Infrapatellar Fat Pad-Synovial Membrane Anatomo-Fuctional Unit: Microscopic Basis for Piezo1/2 Mechanosensors Involvement in Osteoarthritis Pain - Emmi, Aron; Stocco, Elena; Boscolo-Berto, Rafael; Contran, Martina; Belluzzi, Elisa; Favero, Marta; Ramonda, Roberta; Porzionato, Andrea; Ruggieri, Pietro; De Caro, Raffaele; Macchi, Veronica (Frontiers in Cell and Developmental Biology, 2022)
The Infrapatellar Fat Pad (IFP) is a fibro-adipose tissue of the knee recently reconsidered as part of a single anatomo-functional unit (AFU) together with the synovial membrane (SM). Several evidence support the role of this unit in the mechanisms that trigger and perpetuate the onset and progression of osteoarthritis (OA) disease. Additionally, the contribution of IFP-SM AFU in OA-associated pain has also been supposed, but this assumption still needs to be fully elucidated. Within this context, the recent discovery of the mechanoceptive Piezo ion channels (i.e., Piezo1 and Piezo2) in mammals and consciousness on their role in mediating both mechanoceptive and inflammatory stimuli could shed some light on knee OA pain, as well as on the process leading from acute to chronic nociceptive responses. For this purpose, the IFP-SM AFUs of both healthy donors (non-OA IFP-SM AFUs, n=10) and OA patients (OA IFP-SM AFUs, n=10) were processed by histology and immunohistochemistry. After the attribution of a histopathological score to IFP-SM AFUs to confirm intrinsic differences between the two groups, the specimens were investigated for the expression and localization/distribution pattern of the mechanosensors Piezo1 and Piezo2. In addition, the presence of monocytes/macrophages (CD68), peripheral nerve endings (PGP9.5) and neoangiogenesis signs (YAP1) was evaluated for a broad tissue characterization. The study results lead to a better description of the IFP-SM AFU microscopic features in both healthy and pathological conditions, highlighting peculiar differences in the study cohort. Specifically, immunopositivity towards Piezo1/2, CD68 and YAP1 markers was detected at vessels level in the OA- IFP-SM AFUs compartments, differently from the non-OA-group. A correlation with pain was also inferred, paving the way for the identification of new and effective molecules in OA management.